Pragmatic recommendations to improve access to rehabilitation robots, assistive technologies and neurorehabilitation services in Africa: proceedings from ICORR-SASNET Ghana neurorehabilitation workshop, 2024 - Ad Adams, Ebenezer; Riener, Robert; Bouri, Mohamed; Gunther, Isabel; Olaogun, Matthew; Komolafe, Morenikeji A.; Ad Adams, Chinonso A.; Akpalu, Albert; Agoriwo, Mary W.; Ajavon, Leslie W.; Ayodele, Kayode; Sanusi, Ahmad A.; et al. (Frontiers in Stroke, 2025)
The 2024 ICORR-SASNET Ghana Neurorehabilitation Robotics workshop, convened on March 15-16, 2024, in Accra, Ghana, brought together 22 speakers and 27 attendees from nine countries to address the pressing need for enhanced access to neurorehabilitation services and rehabilitation robotics in Africa. Low- and Middle-Income Countries (LMICs) face substantial challenges in providing adequate rehabilitation services. This exacerbates the burden of disability and impedes the recovery and quality of life of individuals with stroke and other neurological conditions. The workshop aimed to: (1) discuss current trends, challenges in neurorehabilitation services and rehabilitation robotics in Africa; (2) identify gaps in access to rehabilitation services and assistive technologies in LMICs; (3) develop strategies for improving access to these services; and (4) promote collaborative efforts and knowledge sharing among health professionals and stakeholders. A purposive sampling method was employed to recruit a diverse cohort of practicing health professionals, policy makers, and a stroke survivor/advocate. The workshop featured expert presentations and discussions centered on three key questions: (1) the current status of stroke rehabilitation in Africa and driving policies, (2) the role of assistive technology and rehabilitation devices in Africa, and (3) strategies for inclusive implementation culminated into 10 targeted recommendations for integrating rehabilitation robotics into conventional therapies. A roadmap was developed, featuring future initiatives, awareness campaigns, and technology transfer programs, with a planned second workshop in 2026, aiming to enhance access and promote sustainable solutions.